Foreword - Vilnensis 2008 9-2, Acta Orientalia Orientalia (Acta Orientalia Vilnensia, 2008)
Iam pleased to know that Vilnius University is publishing a volume containing papers presented at the 2nd Indology conference for the Central and Eastern European region held at Vilnius University on the 24–26 August 2006. There is no doubt that the Indology Department at Vilnius University acted as a wonderful host for the conference and contributed immensely to strengthening the academic and scholarly ties of departments of Indology all over Central and Eastern Europe. The Indology Department in Vilnius can proudly claim to have strengthened the long-lasting relationship between India and Lithuania. The departments of Indology in Central and Eastern Europe have not only facilitated the spread of Indian studies in their respective countries but also reinvigorated and strengthened ties between India and Central and Eastern Europe. They have helped in the widespread dissemination of knowledge about India and expanded scholarly and academic interactions between departments of Indology throughout this region. Today these departments boast of several eminent scholars whose knowledge of Indian subjects, including languages and literature and history and culture, is of a high standard. The study of Indology directly contributes to the importance of India—its history, civilisation and culture—in today’s globalised world. India, and therefore Indology, is also important in the study of the economy, science and technology and for technological exchanges in today’s context. India remains the fourth largest economy in the world in terms of purchasing power parity. The Indian economy is currently growing at the rate of nearly 9 per cent per annum, making it one of the fastest growing economies in the world. India’s foreign trade in 2006–7 is expected to surpass US 200 billion, as compared US 30 billion in the early 1990s. The country’s foreign exchange reserves reached a healthy US196 billion in March 2007. India is one of the most favoured destinations for foreign direct investment—close to US 12 billion a year. For knowledge processing industries, as well as back office processing, India has emerged as a major hub of global research and development analysis and scientific inventions. The strengths of India in the new economy—which consists of information technology, bio-technology, nanotechnology and material sciences—are now known all over the world. Indian manufacturing strength is now coming to fruition and these strengths are visible also in the Central and East European market. Several important investments from India have taken place in the steel, electronics, automobile, pharmaceutical, packaging and information technology sectors, to name a few. It is quite evident that this trend will strengthen in the future. Similarly, trade between India and Central and Eastern Europe is increasing between 20–30 per cent a year and is expected to flourish in the near future as more countries from Central and Eastern Europe join the European Union. India has warmly welcomed the recent accession of Bulgaria and Romania to the European Union. All this makes India not only a viable subject of study for its history and culture but also fascinating for its growing economic, scientific and technological strength. These new developments require added attention. It is essential for the course curriculum of Indology studies to be standardised across Central and Eastern Europe as far as is feasible on the basis of cooperation between the universities of the region. I am glad that a website and a network for this purpose have been set up and are functional, with funding from the Embassy of India in Warsaw. The course curriculum for Indology needs to be updated. The knowledge imparted at the Indology centres needs to be well-rounded and contemporary; this will provide the necessary additional tools to the students to understand not only India’s past glories but also its present strengths and future prospects. The Indian Council for Cultural Relations (ICCR ) and the government of India are convinced that this is the course that centres for Indology studies should follow in Central and Eastern Europe, as well as in other regions of the world. India is no longer a country known only for its ancient literature, drama and complex society. It is a nation on the move. Studies on ancient India and modern India should be complementary. I certainly hope that those who impart the knowledge of Indology will themselves catch up with modern developments to be able to contribute to the betterment of the students, who, in all fairness, deserve up-to-date information and knowledge of India. The papers published in the volume cover diverse areas and they are well researched and documented and could become a useful source of reference material for various institutions who offer courses on India. The organisation of the conference in Vilnius has already given exposure to the strength of Indian studies in Lithuania and Central and Eastern Europe. It is remarkable that during this conference a Central and Eastern European Network of Indian Studies (CEENIS) was founded with the participation of institutions at universities from 10 countries in this region. I would sincerely like to thank the faculty and staff, particularly Prof. Audrius Beinorius, the head of the department, for organising the conference and for publishing this volume. I also wish to place on record sincere appreciation to contributions made by a number of other scholars and professors at the Indology Department in Vilnius, as well as to the scholars from other countries, some of whom participated in the conference, for spreading Indian studies in Central and Eastern Europe over the past few decades. I am certain that the tradition of Indian studies in Central and Eastern Europe will become stronger over the years to come and prove beneficial for Indian and Central and Eastern European relations as well as for the teachers and students engaged in Indian studies in the region. My best wishes are with the faculty, staff, and students of Indian studies all over Central and Eastern Europe. HE Anil WADHWA, Ambassador of India to the Republics of Poland and Lithuania 31 March 2007